Oesophageal squamous papilloma in paediatric population: a single-centre case series - Pamela Hernández-Almeida; Fabián Vásconez-Muñoz; Andrea Vásconez-Montalvo; Nelson Montalvo-Flores; Ligia Redrobán-Armendariz; Edison Aymacaña-Albán (BMJ Publishing Group, 2023)
Purpose Oesophageal squamous papilloma (OSP) is a rare epithelial lesion with an unclear aetiology, found incidentally in upper gastrointestinal endoscopy (UGE). We evaluate the epidemiology, general features and endoscopic and histological characteristics of OSP in children in a single centre.Methods We conducted a retrospective search of 3568 medical records of children under 18 years old who underwent UGE between 2004 and 2022, at Hospital Metropolitano de Quito, Ecuador. We described the general features of 15 patients diagnosed with OSP. Histopathology reports were analysed, including a chromogenic in situ hybridisation (CISH) for human papillomavirus (HPV) 6/11.Results OSP was diagnosed in 15 patients between 10 and 16 years of age, with an estimated prevalence of 0.4%. The gender ratio male to female was 1:1.1. Most patients (n=14) underwent UGE due to abdominal pain. Lesions were found predominantly in the upper and lower part of the oesophagus; 12 patients had isolated lesions, and none of the lesions tested positive for HPV on CISH 6/11 analysis. Additionally, Helicobacter pylori and eosinophilic oesophagitis (EoE) were diagnosed in one patient each.Conclusion Our study describes the clinical features of paediatric OSP in a single centre. The prevalence was similar to that in the adult population but higher than in other paediatric populations, and none of our patients had HPV.